The Prevalence of Minimal Hepatic Encephalopathy in an Outpatient Hepatology Clinic - Eyice, Deniz; Ok, Ayşe Merve; Sonsuz, Abdullah; Şenocak, Mustafa Şükrü; Durak, Meliha Nur; Özdemir, Sebati; Canbakan, Billur; Tuncer, Murat; Hatemi, Ibrahim (Turkish Journal of Gastroenterology, 2023)
Background: Minimal hepatic encephalopathy can only be detected by specific psychometric or neuropsychological tests. We aimed to determine the prevalence of minimal hepatic encephalopathy in a hepatology outpatient clinic of a tertiary center. Methods: A total of 82 patients with chronic liver disease were involved prospectively in this study. Control groups consisted of healthy volunteers (n = 123) and chronic renal failure patients (n = 28). We used 2 different methods to detect minimal hepatic encephalopathy. First method was a battery of 5 psychometric tests (number connection tests A and B, digit symbol test, serial dot test, line tracing test) which was filled by all patients. The second method was critical flicker frequency test. Both methods were used in the whole group (n = 233). We applied linear regression analysis to the results of psychometric tests of healthy volunteers to establish equations to calculate the expected values of each test. Test results of the patients were evaluated according to the expected results obtained from these equations. Results: The prevalence of minimal hepatic encephalopathy detected by psychometric tests and critical flicker frequency test was 13% and 14%, respectively. When the positivity of both tests was deemed necessary to diagnose minimal hepatic encephalopathy, the rate of minimal hepatic encephalopathy was 3.6% (n = 3) in a chronic liver disease patient group. Conclusion: Minimal hepatic encephalopathy is a difficult clinical condition to diagnose, and it is more appropriate to use psychometric tests and critical flicker frequency test together.